MARKETING EFFICIENCY ANALYSIS OF BEEF CATTLE IN ANIMAL MARKET SUKA VILLAGE TIGAPANAH SUBDISTRICT KARO DISTRICT - A A Sidebang; I Sembiring; E Mirwandhono; Hasnudi Hasnudi; M Tafsin (Jurnal Peternakan Integratif, 2017)
Abstract. The purpose of this research is to know marketing institution, marketing channel, marketing function, market structure, market behavior, market performance, marketing cost, marketing margin, marketing profit and marketing efficiency of beef cattle in animal market Suka Village TigapanahSubdistrictKaro District. The research conducted in the animal market of Suka Village TigapanahSubdistrictKaro District from March until April 2017. This research used primary data obtained from observation and interview of respondents. Determination of respondents with snowball sampling method that has 30 respondents. Secondary data is obtained from related institutions such as the Central Agency of Statistics and the Karo District Agricultural Departement. The parameters studied were marketing institution, marketing channel, marketing function, market structure, market conduct, market performance, marketing margin, farmer's share and profit to cost ratio. The results is marketing institutions involved are farmers and agent. The marketing channels are the first two channels: the farmer - the consumer and the second channel: the farmer – the agent - the consumer. Marketing functions undertaken by marketing institutions are the functions of exchange, physical and facilities. The market structure is oligopoly and oligopsoni. Market conduct is the practice of pricing away from dishonesty and marketing costs are not uniform and the absence of intervention from the government. Market performance is that there is no technological progress and no improvement of product quality and service maximization. Marketing margin of cannel I is Rp.0 and channel II is Rp.815.384. Farmer's share of channel I is 100% and channel II is 95.59%. The profit to cost ratio of channel I is 105,86 and channel II is 2,55. The conclusion of this research is the marketing of beef cattle in the animal market of Suka Village TigapanahSubdistrictKaro District has been efficient. Keyword : efficiency, beef cattle, market